Toxicity Reduction of Antiseptic Triclocarban by a Newly Isolated Strain Sphingobacterium sp. MC43 - Merry Krisdawati Sipahutar (School of Postgraduate Studies, Diponegoro Univer, 2024)
Triclocarban, an antimicrobial agent used in pharmaceutical and personal care products, is incompletely degraded during wastewater treatment. However, very little information about biodegradation has been published. This study is the first to describe triclocarban biodegradation and toxicity reduction using Sphingobacterium sp. MC43, a recently discovered plant-growth-promoting bacterium. Sphingobacterium sp. MC43 is a newly isolated strain isolated from agricultural soil with a history of pesticide use. The in vitro characterizations showed that Sphingobacterium sp. MC43 could use triclocarban as the only carbon source and at high concentration (30 μM), whereas phytotoxicity assays were used to evaluate the detoxification of triclocarban. Triclocarban at 30 μM concentration was 50% degraded in less than 72 hours. Sphingobacterium sp. MC43 was able to degrade triclocarban more effectively in recognition to additional carbon sources like acetate, carboxymethyl cellulose, and succinic acid as well as nitrogen sources like sodium acetate and urea. Concerned about triclocarban's harmful effects on plants, Vigna radiata was used to study how Sphingobacterium sp. MC43 can reduce toxicity. Triclocarban exposure caused damage to Vigna radiata plant, whereas Sphingobacterium sp. MC43 bioaugmentation significantly reduced this damage. This is likely because the bacteria's biomass and degrading power have grown. These results imply that this strain has a high triclocarban bioremediation efficiency and potentially reducing triclocarban uptake in Vigna radiata.